Detection and genetic characterization of norovirus in oysters from China and Japan - Phan T.G. (2014)
A total of 225 oysters from China and Japan were collected during October 2005 to September 2006 and were then tested for the presence of norovirus by RT-nested PCR. The detection rate of norovirus was different between China and Japan, accounting for 14.6% (19 of 130) and 25.3% (24 of 95), respectively. In China, norovirus in oyster was detected continuously from July to February with !the highest prevalence in August, October and November (each of 21%, 4 of 19). On the other hand, norovirus in Japan was found year-round with highest prevalence in March and October (each of 20.8%, 5 of 24). Noroviros strains detected were subjected to further characterization by sequence analysis. It was found that the norovirus strains belonged to only two distinct genotypes, the GII/3 (known as the Mexico virus cluster) and the GII/4 (known as the Lordsdale virus cluster). In China, the norovirus GII/4 was the most predominant, accounting for 78.9% (15 of 19). In contrast, it was interesting that both the norovirus GII/4 and the norovirus GII/3 were co-predominant with a prevalence of 50% (12 of 24) in Japan. Another interesting feature of the study was that the norovirus GII/4 strains in oysters from both countries were grouped into two distinct variant clusters known as the Farmington Hills variant and the Hunter variant. More than 102 copies of norovirus were detected in 41 of 43 oysters. This study provided additional evidence of the presence of norovirus in oysters and is also the first report to demonstrate the existence of norovirus variants in oysters.